2011
DOI: 10.1375/twin.14.3.240
|View full text |Cite
|
Sign up to set email alerts
|

An Epidemiological Survey of Post-Coital Psychological Symptoms in a UK Population Sample of Female Twins

Abstract: Postcoital psychological symptoms (PPS) is a virtually unexplored phenomenon in the female population even though women frequently complain about irritability and motiveless crying after intercourse and/or orgasm. The aim of this study was to explore the epidemiology and genetic influences of PPS in a UK population sample of women. 1,489 unselected female twins aged 18–85 completed questions on recent and persistent PPS and potential risk factors. Standard methods of quantitative genetic analysis were used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
18
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 41 publications
4
18
1
Order By: Relevance
“…As a precaution, history of sexual abuse and psychological distress were entered into the first block of the hierarchical multiple regression models as a method of control. Although age was not correlated with any of the FSFI domains except for desire, it was possible that age remained a potential confound due to its previously demonstrated association with sexual difficulties [27]. As a check, the multiple regression analyses were run with and without age included at block 1.…”
Section: Hierarchical Regression Analysesmentioning
confidence: 99%
“…As a precaution, history of sexual abuse and psychological distress were entered into the first block of the hierarchical multiple regression models as a method of control. Although age was not correlated with any of the FSFI domains except for desire, it was possible that age remained a potential confound due to its previously demonstrated association with sexual difficulties [27]. As a check, the multiple regression analyses were run with and without age included at block 1.…”
Section: Hierarchical Regression Analysesmentioning
confidence: 99%
“…A very limited number of recent studies have drawn attention to a previously poorly recognized phenomenon known as postcoital dysphoria (PCD), or “post‐sex blues” [3]. PCD is the experience of negative affect characterized by tearfulness, a sense of melancholy or depression, anxiety, agitation, or aggression following sexual intercourse [4].…”
Section: Introductionmentioning
confidence: 99%
“…[2] reported that 32.9% of the women in their sample had experienced PCD symptoms in their lifetime. A study by Burri and Spector [4] investigated the experience of post‐coital psychological symptoms such as irritability and motiveless crying after sexual intercourse and/or orgasm in a sample of 1,489 female twins in the United Kingdom. They reported 7.7% of women reported experiencing these symptoms persistently and 3.7% of women reported recent experience of these symptoms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we sought to investigate Postcoital dysphoria (PCD) or post-sex blues, which is a form of distress associated with sexual activity, commonly defined as the experience of negative emotions such as tearfulness, feelings of melancholy or depression, anxiety, agitation, or aggression after sexual intercourse [7,8]. Previously, twin studies have revealed that sexual distress has a heritability of 46%, accounting for additive genetic and non-shared environmental factors [8].…”
Section: Introductionmentioning
confidence: 99%